Pengembangan Tata Kelola Wakaf Berbasis Korporasi Di Asia Tenggara/Development The Governance of Corporate-Based Waqf In South East Asia - Huda, Miftahul; Noviana, Lia; Santoso, Lukman (De Jure: Jurnal Hukum dan Syari'ah, 2020)
Abstract:Waqf is still interesting to do a study. Apart from being a form of worship to Allah SWT, waqf is also an instrument of welfare for Muslims. The object of waqf continues to expand. One model of the object of waqf in Muslim countries is the company akaf. This study aims to describe the management and ways of developing corporate waqf in Malaysia and Singapore. This governance is then used as material for the development of corporate waqf in Indonesia. This article is the result of a doctrinal law research with a comparative approach. The results of this study indicate that the company-based waqf concept in Indonesia needs to be developed transformatively. As practice in Malaysia and Singapore. So that it can be an instrument in improving the welfare of the people in a sustainable manner. The formulation of a corporate waqf legal development model in Indonesia needs to be adjusted and strengthened. Regulators as well as an integrative and holistic understanding of the ulama. So that company waqf can be a strategic alternative in an effort to accelerate national economic development.Keywords: waqf, south east Asia, welfare.Abstrak:Wakaf masih menarik untuk dilakukan kajian. Selain merupakan bentuk ibadah kepada Allah SWT, wakaf juga merupakan instumen kesejahteraan bagi umat Islam. Objek wakaf terus mengalami perluasan. Salah satu model objek wakaf di negara-negara muslim adalah wakaf perusahaan. Penelitian ini bertujuan untuk mendeksripsikan pengelolaan dan cara pengembangan wakaf perusahaan di Malaysia dan Singapura. Tata kelola ini kemudian dijadikan bahan pengembangan wakaf perusahaan di Indonesia. Artikel ini merupakan hasil penelitian hukum doktrinal dengan pendekatan perbandingan. Hasil kajian ini menunjukkan bahwa konsep wakaf berbasis perusahaan di Indonesia perlu dikembangkan secara transformatif. Sebagaimana praktik di Malaysia dan Singapura. Sehingga dapat menjadi instrumen dalam meningkatkan kesejahteraan umat secara berkelanjutan. Rumusan model pengembangan hukum wakaf perusahaan di Indonesia perlu disesuaikan dan dikuatkan. Pemangku regulasi sekaligus pemahaman yang integratif dan holistik di kalangan ulama. Agar wakaf perusahaan dapat menjadi alternatif strategis dalam upaya percepatan pembangunan ekonomi nasional.Keywords: wakaf; asia tenggara; kesejahteraan.